1975
DOI: 10.1051/ita/197509r100051
|View full text |Cite
|
Sign up to set email alerts
|

Une double hiérarchie infinie de langages vérifiables

Abstract: AFCET, 1975, tous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Finally we show that open bracket of order n is syntactic of degree 0. The family of checking automata languages [13,20] is closed under open bracket of order n, the regular languages and the context free languages are not closed under these operators. The families of equal matrix languages of order n [23] are easily characterized with open bracket of order n, hence we can conclude that the equal matrix languages are linear erasable.…”
Section: Open Bracket Of Order Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally we show that open bracket of order n is syntactic of degree 0. The family of checking automata languages [13,20] is closed under open bracket of order n, the regular languages and the context free languages are not closed under these operators. The families of equal matrix languages of order n [23] are easily characterized with open bracket of order n, hence we can conclude that the equal matrix languages are linear erasable.…”
Section: Open Bracket Of Order Nmentioning
confidence: 99%
“…These operators allow to build hierarchies of families of languages caused by repeated applications of these operators [2,3,10,11,12,15,19,20,22]. In some cases it was observed that one application (bracket [2], nested iterated substitution [14]) or a finite number of applications [3] of the operator produce the relevant closure of a family.…”
Section: Introductionmentioning
confidence: 97%
“…--E est la famille des langages alg6briques (context-free languages), --E est la famille 6tudi6e par Rodriguez dans [4], qui est un c6ne rationnel v6rifiant P"(E),…”
Section: Introductionunclassified